Antimicrobial Sensitivity Associated with Porphyromonas gingivalis Present in Periodontitis Frameworks: An Integrative Review - , Matéus Simplício Araújo; , Antônio Evandro de Sousa Silva; , Júlio César Sousa Prado (Archives of Current Research International, 2024)
Objectives: The Gram-negative anaerobic bacterium Porphyromonas gingivalis is identified as one of the most important causes of the chronic form of periodontitis. This work aimed to analyze the sensitivity of P. gingivalis to antibiotics and antimicrobial agents. Study Design: Integrative literature review. Methodology: Through a careful analysis of clinical trials published in the last 5 years. A bibliographic search was carried out in the PubMed, Scielo and Google Scholar databases. Three keywords were established and verified on the DeCs-Descritores em Ciências da Saúde website for the literary search “Antimicrobial resistance”, “Periodontal biotherapy” and “Porphyromonas gingivalis”. 66 articles were found. Of these, animal studies, studies that did not involve patients diagnosed with periodontitis according to the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions, and studies on peri-implantitis were excluded. Studies that used only surgical therapy without association with at least one antibiotic or antimicrobial and duplicate studies were excluded. Results: This integrative review presents the results of 19 studies. Amoxicillin, Metronidazole and Azithromycin are the most commonly used antibiotics. Photodynamic therapy has demonstrated benefits in reducing inflammation and P. gingivalis counts. It has been demonstrated that P. gingivalis is not sensitive to Lactobacillus brevis and Lactobacillus plantarum-ProlcSan probiotic gel and tablets, as no reductions in its proportion and total count were observed. Similar results were also observed in the study that investigated the effect of administering piperacillin plus Tazobactam gel and doxycycline gel. Conclusion: Although most of the articles presented report the sensitivity of P. gingivalis to their protocols, microbiological reduction is not always accompanied by clinical benefit, since periodontal disease is multifactorial. Based on these findings, it is concluded that there are several antimicrobial agents capable of promoting the reduction of this key pathogen in periodontitis.